2017
DOI: 10.1590/1981-22562017020.160131
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of elderly patients in Intensive Care Units

Abstract: Objective: Conduct a survival analysis of elderly patients hospitalized in an intensive care unit (ICU), identifying the predictors of mortality among this age group. Methods: A retrospective cohort study was performed with data from the medical records of 457 elderly patients hospitalized in an ICU located in the city of Natal in Brazil. Survival functions were estimated using the Kaplan-Meier estimator, and the Log-rank test was used for comparisons. In addition, a multiple Cox proportional hazards model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
1
13
0
8
Order By: Relevance
“…In one study, it was identified that acute clinical injuries and age over 80 years are associated with mortality in survival studies with follow-up of less than 30 days, and that situations such as lower consciousness level, use of mechanical ventilation and respiratory diseases are factors that worsen this outcome. (11) The mortality of the long-living patients in this study was high (51.6%), and may also be related to the high rates of origin from the emergency unit, with prolonged hospitalization. A large part (24.6%) remained hospitalized for between 11 and 20 days, a longer period when compared to other studies.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In one study, it was identified that acute clinical injuries and age over 80 years are associated with mortality in survival studies with follow-up of less than 30 days, and that situations such as lower consciousness level, use of mechanical ventilation and respiratory diseases are factors that worsen this outcome. (11) The mortality of the long-living patients in this study was high (51.6%), and may also be related to the high rates of origin from the emergency unit, with prolonged hospitalization. A large part (24.6%) remained hospitalized for between 11 and 20 days, a longer period when compared to other studies.…”
Section: Discussionmentioning
confidence: 69%
“…(10) The presence and number of comorbidities found was not related to the outcome death, which was also observed in another study conducted in Rio Grande do Norte with elderly people hospitalized in the ICU. (11) In that study, it was observed that comorbidities and chronic diseases were not related to the survival of the elderly in survival studies with less than 30 days of follow-up; the presence of comorbidities was associated with unfavorable outcomes in the hospitalized elderly though when the follow-up was longer than 30 days.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…5 It is pointed out that the elderly have a longer hospital stay when compared to other age groups and a shorter significant survival, mainly due to senescence-related weaknesses added to the disease process. [6][7][8] It is known that, at the time of hospital discharge, the elderly may present injuries that did not have in their pre-hospitalization state, such as loss and reduction of functional capacity, and lower tolerance to physical activity. It is noteworthy that functional impairment prior to ICU admission may represent a determining condition for an unfavorable outcome in the elderly.…”
mentioning
confidence: 99%